In Vitro Evaluation of Color Changes in CAD/CAM Materials Due to Long-Term Water Aging - Sancak, Elif İ. (2026)
The aim of this study is to examine the discoloration in CAD/CAM materials used in dentistry after 4-years of contact with water, which is the environment to which they are most exposed in the oral cavity. Three different A2-colored resin-based CAD/CAM blocks (Cerasmart, Coltene Brilliant Crios and Shofu Block HC) were used in our study. A total of 180 specimens, 60 of each CAD/CAM material, were prepared with a thickness of 2-mm. Then, each material was divided into three different groups based on the polishing systems (Coltene Diatech, Sof-Lex Diamond, Identoflex Diamond Ceramic) applied in accordance with the recommendations of the manufacturing companies (n:20). The discoloration of the materials on a white background and under natural light sources at the beginning and after being stored in distilled water for 4-years were measured with the VITA EasyshadeV spectrophotometer. All the obtained data were examined using the Kolmogorov Smirnov and Shapiro Wilk Normality Test values. After the water aging process, no statistically significant difference was found between the Cerasmart (p=1.51; p>0.05) and Shofu (p=0.95; p>0.05) CAD/CAM material groups using three different polishing systems. A statistically significant difference was found between all polishing system groups of Coltene CAD/CAM materials (p=0.00). All CAD/CAM materials showed color changes above the ∆E00≤0.8 perceptibility threshold after being aged in distilled water for 4 years. Cerasmart CAD/CAM blocks (Coltene ∆E00=1.33, Sof-lex ∆E00=1.43, Identoflex ∆E00=1.69) showed color changes below the ∆E00≤1.8 acceptability threshold in all groups where different polishing systems were applied, while Coltene (Coltene ∆E00=3.7, Sof-lex ∆E00=3.81, Identoflex ∆E00=4.69) and Shofu (Coltene ∆E00=2.33, Sof-lex ∆E00=1.74, Identoflex ∆E00=1.91) blocks showed color changes above the acceptable threshold value.